Punitive State: Crime, Punishment, and Imprisonment Across the United States - Frost, Natasha (Criminal justice recent scholarship, 2006)
Intro -- CONTENTS -- INTRODUCTION -- ACKNOWLEDGMENTS -- THE PUNITIVE TURN -- UNDERSTANDING THE PUNITIVE TURN -- TRENDS IN IMPRISONMENT -- EXPLORING VARIATIONS IN IMPRISONMENT -- EXPLAINING VARIATIONS IN IMPRISONMENT -- THE PROBLEM WITH PUNITIVENESS -- MEASURING PUNITIVENESS -- PUNITIVENESS ACROSS MEASURES -- PUNITIVENESS ACROSS OFFENSE TYPES -- PUNITIVENESS OVER TIME, 1990-2000 -- UNDERSTANDING VARIATIONS IN PUNITIVENESS -- STATE SPECIFIC DATA ANOMALIES -- SUPPLEMENTAL TABLES -- REFERENCES -- INDEX.